Teleworking from home experiences during the COVID-19 pandemic among public health workers (TelEx COVID-19 study) - Josephine Sau Fan Chow; Dimetrious Palamidas; Sonia Marshall; Wendy Loomes; Suzie Snook; Rebecca Leon (BMC, 2022)
Abstract Background When working from home (WFH) became temporarily necessary for staff as a result of the COVID-19 pandemic in 2020, it had to be implemented without significant organisational experience or understanding of WFH and its complexities. This study aims to determine the impacts experienced by staff who have undertaken WFH during the COVID-19 pandemic. Methods This was an observational cross-sectional study using survey with a purposive sampling strategy for staff from corporate and non-clinical departments. These staff undertook WFH during COVID-19 pandemic in 2020. None of these staff had any direct operational roles in a hospital facility and clinical service. Participants' self-reports of their mood while working in their normal workplace and while WFH were collected via the Scale of Positive and Negative Experience (SPANE), a validated affect balance questionnaire. The responses from the open-ended question were analysed using thematic analysis approach. Results A total of 143 participants completed the survey responses. Majority (61%) WFH for four or more months as a result of the COVID-19 pandemic. Participants rated their skills very highly on the technologies with an average rating of 9 (out of 10) for computer skills, smartphones and videoconferencing/teleconferencing applications. Participants felt WFH was an improvement on normal working, in particular in relation to their ability to concentrate and be productive. The "SPANE" relating to affect balance while WFH was completed by 124 participants (85.7%), resulting in a mean score of 5.45 (S.D. 2.98). The SPANE relating to normal working conditions was completed by 127 participant (88.8%) resulting in a mean score of 2.70 (S.D 3.69). This indicated that while participants' positive emotions typically predominated in both situations, they felt slightly more positive on average with WFH. Over 90% participants reported that they would take the opportunity to WFH again if it were offered. Data obtained from the open-ended questions had complimented the findings of the structure close-ended questions in the benefits of remote working and support for their health and wellbeing. The open-ended questions had provided additional information on challenges which the participants encountered during the WFH experience and their suggested preference to sustain this workplace practice. Conclusions This study highlighted factors that impacted workers' work processes, productivity, physical and mental health well-being while WFH and provided a foundation for considering how to best support a positive WFH experience.